Acid rain footprint three decades after peak deposition: Long-term recovery from pollutant sulphate in the Uhlirska catchment (Czech Republic) - Marx, Anne; Hintze, Simone; Sanda, Martin; Jankovec, Jakub; Oulehle, Filip; Dusek, Jaromir; Vitvar, Tomas; Vogel, Tomas; van Geldern, Robert; Barth, Johannes (Science of the Total Environment, 2017)
Keywords: Catchment; Export; Groundwater; Mass balance; Soil water; Sulphur

A review of CO2 and associated carbon dynamics in headwater streams: A global perspective - Marx, Anne; Dusek, Jaromir; Jankovec, Jakub; Sanda, Martin; Vogel, Tomas; van Geldern, Robert; Hartmann, Jens; Barth, Johannes (Reviews of Geophysics, 2017)
Keywords: Carbon cycle; CO2 outgassing; Headwater catchments; River water chemistry; Stable isotopes

Corrigendum to “Dynamics of dissolved organic carbon in hillslope discharge: Modeling and challenges” (Journal of Hydrology (2017) 546 (309–325), (S0022169416308526), (10.1016/j.jhydrol.2016.12.054)) - Dusek, Jaromir; Vogel, Tomas; Dohnal, Michal; Barth, Johannes; Sanda, Martin; Marx, Anne; Jankovec, Jakub (Journal of Hydrology, 2019)
The authors regret that an error has occurred in the above cited manuscript. The following correction needs to be made: The annual hillslope export of dissolved organic carbon (DOC) in stormflow was smaller than reported by Dusek et al. (2017). While the correct values of the cumulative DOC mass flux were given in Table 3 of the manuscript, they were wrongly converted to per-meter-square exports of DOC, leading to unrealistically high values of DOC export associated with the preferential stormflow (134.8 g C m−2 y−1 in section 4.9 and >100 g C m−2 y−1 in section 5 of the manuscript). The correct values of DOC export associated with preferential stormflow and deep bedrock percolation were 6.1 g C m−2 y−1 and 1.2 g C m−2 y−1, respectively (based on the best behavioral simulation of two growing and two winter seasons). Thus, the predicted DOC export in our study was in the lower range of the values (2–69 g C m−2 y−1) reported by Neff and Asner (2001), who performed field studies in wetland and peatland ecosystems under humid climate. Under conditions of temperate European forest, Kindler et al. (2011) reported mean export of DOC from subsoil of 3.5 ± 1.3 g C m−2 y−1. However, our corrected results still indicate that the contribution of the hillslope DOC export was higher than the amounts reported in the literature under similar geographic conditions. The authors regretfully apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2019-07-09

Corrigendum to manuscript ”Dynamics of dissolved organic carbon in hillslope discharge: Modeling and challenges” (Journal of Hydrology (2017) 546 (309–325), (S0022169416308526), (10.1016/j.jhydrol.2016.12.054)) - Dusek, Jaromir; Vogel, Tomas; Dohnal, Michal; Barth, Johannes; Sanda, Martin; Marx, Anne; Jankovec, Jakub (Journal of Hydrology, 2019)
The authors regret that an error has occurred in the above cited manuscript. The following correction needs to be made: The annual hillslope export of dissolved organic carbon (DOC) in stormflow was smaller than reported by Dusek et al. (2017). While the correct values of the cumulative DOC mass flux were given in Table 3 of the manuscript, they were wrongly converted to per-meter-square exports of DOC, leading to unrealistically high values of DOC export associated with the preferential stormflow (134.8 g C m –2 y –1 in section 4.9 and > 100 g C m –2 y –1 in section 5 of the manuscript). The correct values of DOC export associated with preferential stormflow and deep bedrock percolation were 6.1 g C m –2 y –1 and 1.2 g C m –2 y –1 , respectively (based on the best behavioral simulation of two growing and two winter seasons). Thus, the predicted DOC export in our study was in the lower range of the values (2–69 g C m –2 y –1 ) reported by Neff and Asner (2001), who performed field studies in wetland and peatland ecosystems under humid climate. Under conditions of temperate European forest, Kindler et al. (2011) reported mean export of DOC from subsoil of 3.5 ± 1.3 g C m –2 y –1 . However, our corrected results still indicate that the contribution of the hillslope DOC export was higher than the amounts reported in the literature under similar geographic conditions. The authors regretfully apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2019-08-20

Dynamics of dissolved organic carbon in hillslope discharge: Modeling and challenges - Dusek, Jaromir; Vogel, Tomas; Dohnal, Michal; Barth, Johannes; Sanda, Martin; Marx, Anne; Jankovec, Jakub (Journal of Hydrology, 2017)

Groundwater data improve modelling of headwater stream CO2 outgassing with a stable DIC isotope approach - Marx, Anne; Conrad, Markus; Aizinger, Vadym; Prechtel, Alexander; van Geldern, Robert; Barth, Johannes (Biogeosciences, 2018)
A large portion of terrestrially derived carbon outgasses as carbon dioxide (CO2) from streams and rivers to the atmosphere. Particularly, the amount of CO2 outgassing from small headwater streams is highly uncertain. Conservative estimates suggest that they contribute 36 % (i.e. 0.93 petagrams (Pg) C yr−1) of total CO2 outgassing from all fluvial ecosystems on the globe. In this study, stream pCO2, dissolved inorganic carbon (DIC), and δ13CDIC data were used to determine CO2 outgassing from an acidic headwater stream in the Uhlířská catchment (Czech Republic). This stream drains a catchment with silicate bedrock. The applied stable isotope model is based on the principle that the 13C ∕ 12C ratio of its sources and the intensity of CO2 outgassing control the isotope ratio of DIC in stream water. It avoids the use of the gas transfer velocity parameter (k), which is highly variable and mostly difficult to constrain. Model results indicate that CO2 outgassing contributed more than 80 % to the annual stream inorganic carbon loss in the Uhlířská catchment. This translated to a CO2 outgassing rate from the stream of 34.9 kg C m−2 yr−1 when normalised to the stream surface area. Large temporal variations with maximum values shortly before spring snowmelt and in summer emphasise the need for investigations at higher temporal resolution. We improved the model uncertainty by incorporating groundwater data to better constrain the isotope compositions of initial DIC. Due to the large global abundance of acidic, humic-rich headwaters, we underline the importance of this integral approach for global applications.<br

Hydrochemical and isotopic tracing of runoff generation in the small mountainous catchment Uhlířská (Czech Republic), using the netpath approach - Vitvar, Tomas; Sanda, Martin; Marx, Anne; Hubert, E.; Jancovec, J; Barth, Johannes (Acta Hydrologica Slovaca, 2016)

Modelling multiseasonal preferential transport of dissolved organic carbon in a shallow forest soil: Equilibrium versus kinetic sorption - Dusek, Jaromir; Dohnal, Michal; Vogel, Tomas; Marx, Anne; Barth, Johannes (Hydrological Processes, 2019)
Parameterization of transformation and transport processes of dissolved organic carbon (DOC) in soils is challenging especially under variable hydrological conditions. In this study, DOC concentrations in stormflow were analysed with a physically based modelling approach. A one-dimensional dual-continuum vertical flow and transport model was applied to simulate subsurface processes in a macroporous forest hillslope soil over a period of 4.5 years. Microbially mediated transformations of DOC were assumed to depend primarily on soil moisture and soil temperature. Two conceptually different descriptions of the sorption of DOC to soil were examined with equilibrium and kinetic approaches. In order to quantify the uncertainties associated with the model parameterization, Monte Carlo analyses in conjunction with Latin hypercube sampling was performed. Despite the complexity of microbial transformations, the simulated temporal patterns of DOC concentrations in stormflow showed similar behaviour to those reflected in the observed DOC fluxes. Due to preferential flow, the hillslope DOC export (5.0 ± 0.5 g C · m−2 · year−1) was higher than the amounts usually reported in the literature. Overall DOC transport in hillslope scenarios could be described appropriately using the equilibrium sorption assumption. The performed analyses showed that the inclusion of the kinetic description of DOC sorption only slightly improved the predictions of the DOC hillslope export. Moreover, influences of seasonal hydro-climatological conditions on hillslope export of DOC could be observed. Reduced DOC transport during an extreme warm and dry summer was described with lower accuracy, thus indicating the difficulties in the representation of DOC transformations under dry conditions.
CRIS-Team Scopus Importer:2019-09-03
Keywords: dissolved organic carbon; DOC adsorption/desorption; dual-permeability model; hillslope discharge; kinetic sorption; Monte Carlo analysis; preferential transport; uncertainty